Saudi secondary school science textbooks’ ability to inculcate a PISA-Informed Scientific Identity - Wadha H. Alotaibi; Amani Khalaf H. Alghamdi (PLoS ONE, 2025)
Saudi Arabia’s low performance in the 2018 Programme for International Student Assessment (PISA) science tests (M = 386 compared to M = 489 overall) prompted a content analysis of Saudi secondary school science textbooks (N = 9, three books for each of Grade, 7, 8, and 9) (86% intracoder reliability). Using a definition of scientific identity formed using PISA’s conceptual framework, we recommend future textbook revisions that ensure more balanced coverage to offset the current uneven weighing of scientific knowledge (55%), scientific competencies (28%), and science context (17%). Right now, students receive substantial coverage of major facts, concepts, and theories (knowledge) but less so for competencies (e.g., proficiency in scientific explanations, design, evaluation, and interpretation) or for how to understand and use science in different contexts at different levels (i.e., personal, local, and global). We assumed that secondary students’ appreciation that “science is for me” (i.e., positive scientific identity) will happen, if they are evenly exposed to all PISA dimensions. Because grade level profiles were very similar (both what was present and missing), rebalancing must occur in all three grades. Revised science textbooks that augment current weak spots should positively influence Saudi secondary student’s scientific identity and improve PISA performance.